2018
DOI: 10.1021/acs.jmedchem.7b01898
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships and Therapeutic Potentials of 5-HT7 Receptor Ligands: An Update

Abstract: Serotonin 5-HT receptor (5-HTR) has been the subject of intense research efforts because of its presence in brain areas such as the hippocampus, hypothalamus, and cortex. Preclinical data link the 5-HTR to a variety of central nervous system processes including the regulation of circadian rhythms, mood, cognition, pain processing, and mechanisms of addiction. 5-HTR blockade has antidepressant effects and may ameliorate cognitive deficits associated with schizophrenia. 5-HTR has been recently shown to modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 190 publications
(461 reference statements)
0
22
0
Order By: Relevance
“…AZ-853 and AZ-861 are chemical analogs that differ only in the quality of the fluorine substituent in the phenyl ring attached to piperazine. A small change in the chemical structure may cause differences not only in chemical and physical properties but also in pharmacological and pharmacokinetic characteristics (e.g., paliperidone vs. risperidone) [17][18][19][20]. Our previous investigations revealed that compounds AZ-853 and AZ-861 possess high affinity for serotonergic 5-HT 1A R and are 5-HT 1A R antagonists in CHO-K1 cells in the Ca 2+ mobilization assay, with AZ-861 showing 2-fold higher K b value [8].…”
Section: Discussionmentioning
confidence: 99%
“…AZ-853 and AZ-861 are chemical analogs that differ only in the quality of the fluorine substituent in the phenyl ring attached to piperazine. A small change in the chemical structure may cause differences not only in chemical and physical properties but also in pharmacological and pharmacokinetic characteristics (e.g., paliperidone vs. risperidone) [17][18][19][20]. Our previous investigations revealed that compounds AZ-853 and AZ-861 possess high affinity for serotonergic 5-HT 1A R and are 5-HT 1A R antagonists in CHO-K1 cells in the Ca 2+ mobilization assay, with AZ-861 showing 2-fold higher K b value [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical evaluation has shown that JNJ-18038683 significantly increased the time of REM sleep episode compared to placebo and reduced total REM sleep time. These data demonstrated that the effect of 5-HT 7 receptor blockade induced by JNJ-18038683 on REM sleep is translated from rodents to humans [26,57]. JNJ-18038683 is now undergoing a phase II clinical trials as adjunctive treatment to improve cognition impairment and to alleviate depressive symptoms in stable bipolar patients [57].…”
Section: -Ht 7 Receptor For Insomniamentioning
confidence: 96%
“…These data demonstrated that the effect of 5-HT 7 receptor blockade induced by JNJ-18038683 on REM sleep is translated from rodents to humans [26,57]. JNJ-18038683 is now undergoing a phase II clinical trials as adjunctive treatment to improve cognition impairment and to alleviate depressive symptoms in stable bipolar patients [57]. Kim et al [27] have discovered Azepine…”
Section: -Ht 7 Receptor For Insomniamentioning
confidence: 99%
“…TP-22 exhibited 5-HT7R agonist properties (Table 1) and improved in vitro metabolic stability as compared to LP-211 (half-life = 45 min and 15 min, respectively; Lacivita et al, 2016). TP-22 was able to stimulate neurite outgrowth in neuronal primary cultures in shorter time and at a lower concentration than LP-211, showing a comparable in vivo bio-distribution profile (brain C max 515 ng/mL and 540 ng/mL, respectively; Lacivita et al, 2016; Modica et al, 2018). Starting from the evidence that the administration of methylphenidate (MPH) causes an upregulation of 5-HT7Rs (Adriani et al, 2006; Leo et al, 2009), and in light of the several findings that propose a physiological role for 5-HT in reward guided behavior (Broderick and Phelix, 1997; Luo et al, 2016; Fischer and Ullsperger, 2017), we formulated the hypothesis that a previous administration of a 5-HT7 agonist could have modulatory effects on the well-known rewarding and stimulant MPH effects.…”
Section: Introductionmentioning
confidence: 96%